CFD-based optimization of compressor room ventilation in automotive manufacturing - Arissaputra, Sofian; Damanik, Syalsa Saliha; Herdimas, Muhammad (JTTM : Jurnal Terapan Teknik Mesin, 2026)
This study aims to evaluate the performance of an industrial compressor room ventilation system through an integrated approach combining SNI 03-6572-2001, Building Information Modelling (BIM), and Computational Fluid Dynamics (CFD). The research methodology consists of standard-based ventilation sizing, BIM-based spatial modeling, CFD simulations of airflow and thermal conditions, and validation using field measurement data. The results indicate that the reconfiguration of the ventilation system significantly improves airflow distribution and reduces indoor temperature, leading to a decrease in compressor motor operating temperature and electrical current consumption. These improvements contribute to enhanced energy efficiency and measurable carbon emission reduction. This study provides a systematic and replicable framework for ventilation performance assessment in industrial compressor rooms and supports energy-efficient design strategies aligned with the Sustainable Development Goals (SDGs).